Family MUAC supported by a two-way SMS platform for identifying children with wasting: the Mama Aweza randomised controlled trialResearch in context - Kirkby D. Tickell; Cathering Achieng; Mary Masheti; Maureen Anyango; Agnes Ndirangu; Mareme M. Diakhate; Emily Yoshioka; Carol Levin; Arianna Rubin Means; Esther M. Choo; Keshet Ronen; Jennifer A. Unger; et al. (EClinicalMedicine, 2023)
Summary: Background: Effective methods of preventing and identifying childhood wasting are required to achieve global child health goals. Family mid-upper arm circumference (MUAC) programs train caregivers to screen their child for wasting with MUAC tapes. We assessed the effectiveness of a two-way short message service (SMS) platform (referred to as the Maternally Administered Malnutrition Monitoring System [MAMMS]) in western Kenya. Methods: In this individual-level randomised controlled trial in two rural countries in western Kenya, children (aged 5–12 months) were randomly allocated (1:1) to receive either standard care (SOC) or MAMMS. Randomisation method was permuted-block randomisation with a block size of 10. Eligible participants were children attending maternal child health clinics in the two counties whom had a MUAC between 12.5 and 14.0 cm. The MAMMS group received two MUAC tapes and weekly SMS reminders to screen their child's MUAC. The SOC group received routine community health volunteer services and additional quarterly visits from the study team. The primary analysis used a cox proportional hazards model to compare SOC and MAMMS time-to-diagnosis of wasting (MUAC <12.5 cm) confirmed by a health professional during 6-months follow-up. Secondary outcomes were days from enrolment to treatment initiation among children with wasting, proportion of all children with wasting who were identified by the two approaches (treatment coverage), mean MUAC at treatment initiation, and duration of wasting treatment. This trial was registered on ClinicalTrials.gov, NCT03967015. Findings: Between August 1, 2019 and January 31, 2022, 1200 children were enrolled, among whom the incidence of confirmed wasting was 37% lower in the MAMMS group (hazard ratio: 0.63, 95% CI: 0.42–0.94, p = 0.022). Among children with wasting, the median number of days-to-diagnosis was similar between study groups (MAMMS: 63 days [interquartile range (IQR): 23–92], SOC: 58 days [IQR: 22–94]). Treatment coverage in the MAMMS group was 83.3% (95% CI: 39.9–100.0) while coverage in the SOC group was 55.6% (95% CI: 22.3–88.9%, p = 0.300). Treatment duration and mean MUAC at treatment initiation were similar between groups. Interpretation: Family MUAC supported by SMS was associated with a 37% reduction in wasting among young children. Empowering caregivers to monitor their child's nutritional status at home may prevent a substantial proportion of moderate wasting. Funding: Thrasher Research Foundation and Pamela and Evan Fowler.